Short sleep duration is linked with short stature and delayed age of menarche in Indonesian boarding school girls - Rayi Kurnia Perwitasari; Yuni Hisbiyah; Nur Rochmah; Muhammad Faizi (Human Biology and Public Health)
Background Several factors directly and indirectly influence child growth. Menarche is the initial menstrual period that is regulated by the hypothalamic-pituitary-gonadal axis. Both growth and menarche are affected by biological, genetic, epigenetic, nutritional, and psychosocial factors. Boarding schools are assumed to encourage responsibility and maturity in children, but boarding schools are also reported to have less sleeping duration.